Polymorphisms rs4673 and rs28714259 in predicting anthracycline-mediated cardiotoxicity in patients with breast cancer - Gvaldin, Dmitry; Timoshkina, Nataliya; Vladimirova, Lyubov; Svetitskaya, Yana; Vaschenko, Larisa (Klinicka onkologie, 2021)
INTRODUCTION: Against the background of significant progress in anticancer therapy, which makes it possible to improve the quality of life and life expectancy of patients with cancer, anthracycline antibio-tics retain their relevance, both for scientific research and for clinical practice. However, the therapeutic efficacy of anthracyclines is associated with the development of various complications, among which the most common is cardiotoxicity. Our study was dedicated to searching for possible associations between rs4673 and rs28714259 single nucleotide polymorphisms (SNPs) and the risk of cardiotoxicity in breast cancer patients who underwent anthracycline-containing chemotherapy. MATERIALS AND METHODS: The study included 256 patients with a dia-gnosis of breast cancer without dia-gnosed cardiovascular changes who were treated at the National Medical Research Center of Oncology in Rostov-on-Don in 2019-2020. For SNP genotyping, DNA was extracted from blood and high resolution melting analysis was performed. The presence of SNPs was confirmed by Sanger sequencing. RESULTS: The presence of the T-allele rs4673 increased the risk of cardiotoxicity in breast cancer patients 6.49x (95% CI 1.48-28.53; P = 0.002), and the presence of the A-allele rs28714259 increased the risk 3.27x (95% CI 1.23-8.75; P = 0.026). For tests based on genotyping rs4673 and rs28714259 SNPs, the areas under the receiver operating characteristic (ROC) curves were equal to 71.9% and 76.3%, respectively. The two-locus SNP-SNP model turned out to be statistically significant: the training balanced accuracy was 0.77; similarly, the testing balanced accuracy, and the cross-validation consistency was 10/10. CONCLUSION: Our study confirmed the predictive value of genetic tests based on the determination of the rs4673 and rs28714259 SNPs. Genotyping of both SNPs will significantly improve the accuracy of predicting the development of cardiotoxicity against the background of anthracycline-containing therapy and timely identify the risk group of breast cancer patients for whom it is necessary to adjust the therapeutic strategy.
Keywords: senioři; NADPH-oxidasy; Breast Neoplasms; Cardiotoxicity; kardiotoxicita; jednonukleotidový polymorfismus; Anthracyclines; SNP-SNP interactions; breast cancer; Middle Aged; NADPH Oxidases; rs28714259; Adult; mladý dospělý; Young Adult; ženské pohlaví; Humans; Antibiotics, Antineoplastic; lidé středního věku; Risk; nádory prsu; riziko; antracykliny; protinádorová antibiotika; dospělí; Female; Aged; anthracycline-mediated cardiotoxicity– rs4673; lidé; Polymorphism, Single Nucleotide